Development of "Action Free" electricity saving - Muhammad Zaki Ab Raffar @ Ab Khafar (Universiti Malaysia Perlis, 2009)
Saving or reduction of an electricity is highly popular now. Base on the project title, it includes concept on how to reduce the monthly rate of energy consumption specifically to air conditioner system. Air conditioners use 66% of the total daily peak activity of electricity. This information shows that air conditioner system contributes the highest electricity consumption. The proposed concept is to undertake a task from human lacks such a careless to switch off the air conditioner. Then, movement detector is proposed. Movement detector has great potential because it efficiency of resource, reliable and low production cost. This technology is used in the industry because it high efficiency. A concept that has being purpose in this context is applicable in energy saving of air conditioning applies in UniMAP. There was several calculation and experiment result based on the concept proposed. Those experiments were carried out in UniMAP campus. Overall, based on data collected from those experiments shows that the concept has being purposed capable to increase an air conditioning system efficiency.